IgE‐mediated allergy to pholcodine and cross‐reactivity to neuromuscular blocking agents: Lessons from flow cytometry1. Issue 2 (25th January 2013) - Leysen, J.; De Witte, L.; Sabato, V.; Faber, M.; Hagendorens, M.; Bridts, C.; De Clerck, L.; Ebo, D.
Abstract: Background: : Immunoglubulin E antibody‐mediated allergic reactions to opioids are rare and difficult to document correctly. Objective: : Assessment of the basophil activation test in the diagnosis of IgE‐mediated allergy to the antitussive pholcodine and associated sensitizations to neuromuscular blocking agents (NMBA). Methods: : Three patients with a suspected IgE‐mediated allergy to pholcodine were investigated using skin tests, quantification of specific IgE, and flow cytometric activation of basophils. Results and conclusion: : Flow cytometric activation of basophils, with simultaneous analysis of CD63 appearance and median histamine content per cell, is the only technique capable to correctly document pholcodine allergy. The negative predictive value of basophil activation tests might help to elucidate on the controversial putative cross‐reactivity between pholcodine and NMBA. © 2013 International Clinical Cytometry Society